Operative and Perioperative Durations in O-Arm vs C-Arm Fluoroscopy for Lumbar Instrumentation. Issue 3 (25th July 2017) - Knafo, Steven; Mireau, Etienne; Bennis, Saad; Baussart, Bertrand; Aldea, Sorin; Gaillard, Stephan
Abstract: BACKGROUND: Intraoperative 3-dimensional fluoroscopy (eg, O-arm) has been shown to improve accuracy of pedicle screw placement over 2-dimensional fluoroscopy (C-arm), but its effect on surgery duration remains unclear. OBJECTIVE: To compare the durations of operative and perioperative times between O-arm and C-arm procedures for degenerative lumbar disorders. METHODS: We analyzed 198 patients representing 987 pedicle screws treated in a single center by 4 different surgeons between 2013 and 2015. Accuracy of pedicle screw placement was assessed using the Laine classification on postoperative CT scans. Operative and perioperative durations were prospectively reported on the procedure sheet by anesthesiologists. RESULTS: As expected, placement of pedicle screws using O-arm navigation was overall more accurate compared to C-arm fluoroscopy (strictly intrapedicular screws: 549/663 = 82.8% vs 239/324 = 73.8%, P  = .008). This benefit did not depend on surgeon individual performance ( P  = .17). Average operative duration per instrumented level was significantly shorter in the O-arm group (57.3 min vs 66.1 min, P  = .02) but also depended on the surgeon, indication, and interbody fusion. However, only surgeon individual performance remained significantly associated with surgery duration in multivariate analysis ( P  < .001). Similarly, the only factor that remained significantly associated with longer perioperative durations in multivariate analysis was the indication of surgery ( P  < .001). CONCLUSION: This study shows that O-arm navigation does not independently decrease operative duration, nor increases perioperative time, while improving accuracy of pedicle screw placement.